The Back Mutation in Amitav Ghosh’s The Hungry Tide - Fırat Yıldız (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
This study aims to focus on the back mutation process of the protagonist, Piyali Roy. Piya has migrated to United States with her family during the post colonization process. There are many motives that lie behind the migration to another country. Colonization process also has a role in the practice of migration. As a postcolonial writer Ghosh, represents a story that takes place after the colonization process. As a result of migration the cultural conflicts causes some problems in Piya’s approach to her original culture and language. At the beginning of the novel she appears as a young American who is on a work trip. She works as a cetologist in other words she is a researcher of marine animals. She is back to her country of origin, Bengal, to work on a special species of dolphins. In a Bengali setting, excluding her skin color, she appears as a complete American. She does not look Indian. Her foreignness is stamped in her posture, the way she stands, she moves and her appearance seems out of place. She seems lost in the setting until she meets the deuteragonist, Kanai Dutt. As the two characters start a dialogue it becomes clear that Piya is ignorant of her mother tongue. She is given a Bengali name but she does not know the language. She does not show any interest in intimacy to Bengali. It indicates that she has forged some barriers between her identity and the mother tongue. Piya has internalized the concept of being an American citizen. She is reluctant to be identified with any Bengali element. She feels as a foreigner in Bengal and somehow she is contended with this feeling. Piya’s adventure in Bengal and her friendship with Fokir causes profound changes in her character. The Piya at the beginning and the Piya at the end of the story are totally different from each other. At first a character that ignores her mother tongue, culture and tradition is on the scene. But by the end of The Hungry Tide, Piya appears with a serene soul. She has made peace with her cultural values. She is willing to embrace her mother tongue and culture. This study names Piya’s metamorphosis as ‘back mutation’. Though there is not any expression of Ghosh which indicates this intention evidently. But the general frame of the story represents the possibility of such a subconscious intention. A person can be assimilated in a new culture. But in respect to the case of Piya, it can be suggested that Ghosh has an inner reaction to the concept of turning back to original values and culture. The peaceful end of the story, Piya’s decent state of mind and her determination to start a new life in her culture can support this claim. As her back mutation completes, she embraces her cultural values and as a result Ghosh graces her with a decent place. As a conclusion it can be claimed that one of the most important messages that Ghosh gives in The Hungry Tide is conservation of traditional and cultural values